EFEKTIFITAS PERAWATAN TALI PUSAT DENGAN TEHNIK TERTUTUP DAN TERBUKA TERHADAP PENYEMBUHAN LUKA TALI PUSAT PADA BAYI BARU LAHIR DI RSIA FAUZIYAH TULUNGAGUNG - Ratna Kholidati; Indah Rohmawati (coba, 2019)
Introduction : String center of newborn baby represent wet hurt and can become his entrance is germ so that require to be done by treatment of string center. Since long time treatment of string center a lot of using techniques treatment closed with giving compress of kassa of alcohol 70 %. In this time start a lot of developed opened techniques with do not give any later then the string center let to be opened. But to date not yet been known by storey level of affectivities from the techniques second to healing of hurt of string center newborn baby. Method : Design of at this research is Quasy Eksperimental (Post Test Only Control Group Design). Population of its Goals is borne by new baby is a space copy RSIA Fauziyah Tulungagung and sampel of newborn baby is which is taken care of in space perinatologi, age of pregnancy a term, in order to his score 7 - 10, weight of body born between 2500 gr - 4000 gr and have address to in town Bondowoso. Sum up responder 20 baby consisted of by 10 responder for the closed techniques treatment and 10 responder for treatment of techniques opened. His sampling is Non Probality Sampling ( Consecutive Sampling) with analysis of its data use statistical test of Mann Withney U Test, with storey level of meaning 5%. Result : Result of research indicate that opened to techniques treatment have affectivities of equal to 60 % closed by techniques medium of affectivities of equal to 30 %. This difference is possible caused by a center string condition which tend to damp at closed techniques. From statistical test analysis Mann Witney U Test to show value p = 0,280 (> 0,05), value U = 35 (> 19) and assess Z = - 1,314 , ± 1,96) so that HO accepted and HI refused, His meaning there no difference affectivities of between closed techniques treatment and opened to string hurt healing center newborn baby. Conclussion : There are some constraint in this research for example : 1). Antibiotic resistance related to make the antibiotic within gravida, 2). Responder which is a few. As suggestion from this research result is researcher suggest remain to use techniques of treatment opened for the string treatment center newborn baby because the umbilical dry be quickly and not damp. But for the copy case by resistor because risk of the happening of clear infection there is and techniques higher hence the treatment closed require to be considered.